Analisis Rantai Pasok, Margin dan Efisiensi Saluran Pemasaran Beras di Kabupaten Bone - Hasrullah, Excelsia Ramadhany; Munizu, Musran; Fudjaja, Letty; Hasrullah, Hasrullah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This study aims to identify and examine the pattern or mechanism as well as the role of the rice supply chain in Bone District and to analyze the size of the margin and the efficiency of the rice marketing channel in Bone District. This research took place in four districts, namely Awampone District, Sibulue District, Barebbo District and Bengo District, Bone Regency which is one of the potential food crop production centers. The method used in this study is a qualitative analysis approach and quantitative analysis. Respondents were 30 farmers, marketing agency informants in the study consisted of 4 milling informants and 5 trader informants. Target supply chain patterns, the role of supply chain actors, marketing margins and marketing efficiency are the main discussions in this study. The conclusion in this study is that there are five actors in the supply chain process in Bone Regency, namely farmers, millers, collector traders, retailers and inter-island retailers. The results of the analysis of rice marketing in Bone Regency show that there are three types of marketing channels, namely: marketing channel I, direct farmers to consumers. Marketing channel II, from farmers to collectors (milling) then to retailers, then to consumers. Marketing channel III, from farmers to collectors (milling) then to inter-island retailers, then to consumers. marketing channel margin I does not exist, marketing channel II margin is IDR 6,800/kg, and marketing channel III margin is IDR 9,300/kg. And the existing marketing channels in Bone Regency have been efficient for farmers.